KORELASI ANTARA EFEKTIVITAS PELAKSANAAN SISTEM MANAJEMEN MUTU ISO 9001:2008 DENGAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM DI MAN YOGYAKARTA 1 - Moh Solikul Hadi (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2016)
The problems that exist are ideally students who have met their needs or satisfaction he will be highly motivated to learn Islamic Education. But the fact is, when students have met their needs but still have little motivation to Islamic Religious Education. Therefore, conducted research on the Correlation Between the Effectiveness of Quality Management System ISO 9001: 2008 with PAI Student Motivation “. The results showed that: 1) The level of motivation to learn PAI class XI student inMAN Yogyakarta 1 classified in the high category with an average value of 89.76 and the provisions of respondents who are in a category quite as much as 6 respondents, high and very high 26 respondents 84 respondents , 2). Management System effectiveness of the implementation of ISO 9001: 2008 belongs in effectively with the average value of 86.85 and the provision of students who are in the category of less effective in 3 respondents, quite effective 57 respondents, 47 respondents effective, very effective 9 respondents. 3) There was a significant positive correlation between the effectiveness of the implementation of the quality management system ISO 9001: 2008 with the motivation to learn PAI class XI student in MAN Yogyakarta 1 with rcount (0.362)> rtable (0.195). This means that the effective implementation management system ISO 9001: 2008 will be higher the students’ motivation